Developing a Model of English Listening Materials Using Total Physical Response Method - Nurliana nurliana (EDUVELOP, 2019)
This research was intended to develop a model of English listening materials using Total Physical Response method for the fourth-grade students of SD Negeri 8 Menteng Palangka. Research and Development (R&D) was the method used in this research. The procedure of this research consisted of eleven steps adapted from Sugiyono’s model: 1) Distributing questionnaires in need assessment, 2) Analyzing the result of questionnaires, 3) Reference of the research, 4) Developing the model of the materials, 5) Validating the model of the materials, 6) Revising the model of the materials, 7) Trying-out of the model, 8) Distributing questionnaires & interviewing, 9) Analyzing the result of questionnaires & interview, 10) Revising the tried-out model, and 11) Producing the final version of the materials. The data obtained were analyzed and described qualitatively. The final product of this research was a model of English listening materials using Total Physical Response method consisting of two units with the following topics: 1) Things in Classroom, and 2) Parts of Body and Face. Each unit consisted of eight parts. Each part consisted of three commands. Based on the research findings, it could be concluded that the model of the developed materials was appropriate with the students’ needs.